(untitled) (World Economics and Finance Bulletin, 2022)
The research aims to measure the quality of accounting disclosure in a sample of banks listed in the Iraqi Stock Exchange, with a statement of the most important factors affecting the quality of accounting disclosure, which can ultimately affect the value of the company and the decisions of investors. The research was applied in the Gulf Commercial Bank for the period (2016- 2020). The quality of profits in this bank was measured with the identification of the most important factors affecting them. The research reached a set of conclusions, the most important of which was that there is a possibility to measure the quality of accounting profits of Iraqi banks, and there are a number of factors affecting the quality of accounting profits, which are the size of the economic unit, operational cash flow and return on investment, in addition to that improving the quality of accounting profits can Positively affects the value of the company and the decisions of investors